Isotype diversity of antibodies specific for component allergens in the context of allergic diseases: eosinophilic esophagitis (EoE), asthma, and the alpha-gal syndrome (AGS) - Thomas A. E. Platts-Mills; Matthew H. MacCallum; Jeffrey M. Wilson; Lisa J. Workman; Elizabeth A. Erwin (Frontiers in Allergy)
From the earliest days of studying the reagins in allergic sera that give rise to the Prausnitz-Kuestner reaction, there was evidence that there were other types of antibodies (Ab) specific for allergens, particularly those induced by immunotherapy. By 1980, not only was IgE recognized and could be measured, but the presence of other isotypes including IgG and IgA in patients with IgE was well established. From that time onwards the development of monoclonal antibodies made it possible to distinguish and measure antibodies of other isotypes such as IgG4, IgG2, and IgG3. Over the past 40 years two things have dominated the field- firstly, the techniques for measuring isotype specific antibodies to allergens have improved steadily. Secondly, several different allergic diseases or phenomena have been identified in which isotype diversity of the antibodies has become a major issue. Prior to 1990 only occasional cases of eosinophilic esophagitis (EoE) had been identified, but since then they have become common. Most of the cases have positive skin tests and/or IgE Ab to cow's milk or wheat, but it became obvious that most cases of EoE are not primarily related to IgE. Today it is clear that IgG4 Ab to these allergens play a significant role in cases of EoE. In 2000 the first reports of children developing tolerance to cat allergen appeared. Today it is clear that this tolerance depends on high levels of IgG4 antibodies and there is increasing evidence that the IgG4 response is primarily against Fel d 1. The most recent novel allergic disease is the alpha-gal syndrome (AGS). This condition is based on IgE antibodies specific for the oligosaccharide galactose alpha,1-3-galactose, which are primarily induced by tick bites. However, in this case it was already well known that all immunocompetent primates have made IgG and IgM antibodies to this oligosaccharide. Furthermore, it is not clear whether the IgG isotypes, particularly IgG1 and IgG3, play a role in the inflammatory response to the oligosaccharide. Overall, it is clear that current and future investigation of allergic diseases requires careful assessment of allergen specific antibodies of diverse isotypes in addition to IgE.